2008
DOI: 10.1007/s00266-008-9263-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copaifera langsdorffii Desf. on Ischemia-Reperfusion of Randomized Skin Flaps in Rats

Abstract: The oil-resin of copaíba presents discrete antilipoperoxidation action, intense antioxidant action, and antiinflammatory activity during the ischemia and reperfusion of randomized cutaneous flaps. The effects of ischemia-reperfusion are complex and substances capable of increasing the tolerance of tissue to those effects by reducing the production or neutralizing the action of free radicals are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 23 publications
2
14
0
2
Order By: Relevance
“…In this study, COR treatment also reduced myeloperoxidase activity, further confirming the specific actions of COR treatment on neutrophil recruitment [18]. Anti-inflammatory effects of COR were also observed following experimental pleurisy [17] and skin flap reperfusion-ischemia [31] in rodents.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, COR treatment also reduced myeloperoxidase activity, further confirming the specific actions of COR treatment on neutrophil recruitment [18]. Anti-inflammatory effects of COR were also observed following experimental pleurisy [17] and skin flap reperfusion-ischemia [31] in rodents.…”
Section: Discussionsupporting
confidence: 74%
“…Studies have shown that the beneficial effects of Copaiba are due to its antiinflamatory, antitumor, antitetanus, antiseptic and antiblenorrhagea properties. Usually, the resin is administered orally in natura, or applied in ointment form (Paiva et al , 2002; Biavatti et al , 2006; Silva et al , 2009). By reason of its traditional and widespread use, commercialization of Copaiba as an oil or in capsule form has become intense, to the point of being exported to other countries, such as France, Germany and the United States (Veiga and Pinto, 2002; Veiga et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have found in the Brazilian flora some substances with potential healing effect in colonic anastomosis 2,15 , but the results are not yet considered completely safe. In contrast, Copaíba Oil, which has long been used in the Northern and Northeast Brazil for different therapeutic purposes, such as anti-inflammatory, healing of wounds and laxative [8][9][10] has been gaining attention in the scientific community and has been target of numerous studies on their physicochemical properties with the aim to develop drugs capable of stimulate the surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated clear therapeutic effects of this oil as an inflammation inhibition agent, healing process accelerator in open wounds and even antinociception 8,9,10 . In that area, new lines of research have been developed to analyze the Copaíba oil chemicals components associating them with their pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%